Basic of construction contracts: PAM, CIDB, PWD and FIDIC standard forms / Nor Ainah Abdullah - Abdullah, Nor Ainah (UiTM Press, 2022)
There are many standard forms of contract in use in the construction industry. For students studying towards careers in the industry, to understand all the standard forms can be a daunting prospect. This book is intended as a helpful guide to the basics of construction contracts and the context of the standard forms. The standard forms under discussion are the local building forms (PAM, CIDB and PWD standard forms for buildings) and the international civil engineering form (FIDIC Red Book). While the building standard forms contain closely similar provisions, the engineering form has a different approach and content but there are some surprisingly common provisions with that of the building forms. The material is arranged under topic headings, for example, contract documents, variations, commencement and completion, time and money extensions etc., where the effect of the clauses can be gathered together. It tries to explain, as simply as possible, the rights and duties of the contracting parties and others named in the contract, and the procedures and tasks expected of them to get through a project successfully. Usually, it falls to the contract administrator to settle time, money and quality matters under the contract, and this means he (and everybody else) must know the practical effects of the terms in the contract and the relevant law.